63.9k views
2 votes
Find the equivalent equation that results from, halving both sides first and then subtracting

1 from both sides. Show each step. You do not have to solve the equation at the end,

User Mosammat
by
4.3k points

1 Answer

3 votes

Answer:

6x - 1 = 9

Explanation:

1. first you have to divide every term in the equation by 2

12x/2 + 4/2 = 20/2

2. simplify

6x + 2 = 10

3. next you have to subtract one from both sides

6x + (2-1) = (10-2)

4. simplify

6x + 1 = 9

User Kptlronyttcna
by
4.9k points